Phytochemicals and Aroma Compounds Content of Crabapple (Malus tribolata C.K. Schneid.) Genotypes in Kahramanmaraş Province - Selma Boyacı; Akide Özcan; Mehmet Sütyemez; Şakir Burak Bükücü; Nesibe Ebru Kafkas (Turkish Journal of Agriculture: Food Science and Technology)
Crabapple (Malus tribolata C.K. Schneid.), which one of the rare wild fruit trees in Turkey. This study was carried out to determine the aroma compounds, phenolic compound, antioxidant capacity and some fruit properties of fruits obtained from 2 different crabapple genotypes. The amount of phenolic substance was done by Folin-Ciocalteu method; antioxidant analysis was done using DPPH technique. With respect to antioxidant capacities, the highest value (70.12%) was determined in 46 EL 01 genotype. We found that 46 EL 01 genotype had the highest total phenolic content (839.13 mg/100 g). Determination of volatile compounds that play a major role in fruit quality using the HS-SPME/GC/MS technique, total of 37 aroma compound, namely 7 alcohols, 2 terpenes, 5 aldehydes, 17 esters, 1 ketone, 3 acids and 2 other compounds, were found in two different crabapple genotypes. Total aroma compounds in 46 EL 01 and 46 EL 02 genotypes were calculated as 101.78 μg/L and 102.26 μg/L, respectively. As a result, it has been determined that crabapple, which is a wild fruit, has high phenolic and antioxidant contents and also has many aroma compounds.